2018
DOI: 10.12659/msm.909811
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Type VI Alpha 3 Chain Promotes Epithelial-Mesenchymal Transition in Bladder Cancer Cells via Transforming Growth Factor β (TGF-β)/Smad Pathway

Abstract: BackgroundCollagen type VI alpha 3 chain (COL6A3) has been proven to be a biomarker in the occurrence and development of bladder cancer, which is the most common malignant tumor in the urinary system. This study aimed to explore the effect and molecular mechanism of COL6A3 on EMT in vitro induced by TGF-β/Smad in bladder carcinoma.Material/MethodsThere were 42 patients included in the Kaplan-Meier survival analysis. A cell counting kit-8 (CCK-8) assay and an angiogenesis assay were used to measure cell prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 50 publications
(42 reference statements)
2
24
0
Order By: Relevance
“…Huang et al showed that expression of COL6A3 is increased in bladder tumors, stimulates proliferation and angiopoiesis as well as epithelial-mesenchymal transition, with possible involvement of TGF-β. COL6A3 silencing resulted in reduced expression of TGF-β as well as phosphorylation of SMAD2 and SMAD3 [211]. Trim59, the expression of which is upregulated in bladder tumors, promotes proliferation, EMT, migration, and invasion of bladder cancer cells.…”
Section: Bladder Cancermentioning
confidence: 97%
“…Huang et al showed that expression of COL6A3 is increased in bladder tumors, stimulates proliferation and angiopoiesis as well as epithelial-mesenchymal transition, with possible involvement of TGF-β. COL6A3 silencing resulted in reduced expression of TGF-β as well as phosphorylation of SMAD2 and SMAD3 [211]. Trim59, the expression of which is upregulated in bladder tumors, promotes proliferation, EMT, migration, and invasion of bladder cancer cells.…”
Section: Bladder Cancermentioning
confidence: 97%
“…In addition, COL6A3 may be involved during the EMT process induced by TGF-β/Smad. COL6A3 silencing inhibits cell proliferation and angiopoiesis [ 65 ], which is consistent with COL6A3 having a lower mutation rate in SCE_H and SCE_M, and a higher mutation rate in SCE_L. Additionally, activation of the hypoxic pathway helps cancer cells to be more adaptable to the hypoxic environment.…”
Section: Discussionmentioning
confidence: 57%
“…TGF-β activates SMAD signaling and induces EMT in CRC cells. TGF-β, a multifunctional cytokine, can induce EMT in tumor cells via both SMAD-dependent and SMAD-independent activation of EMT-related transcription factors (21,22). Firstly, it was confirmed that 10 ng/ml TGF-β could activate classic SMAD signaling in CRC cells.…”
Section: Adspred2 Inhibits the Emt Of Crc Cells In Vitromentioning
confidence: 88%
“…EMT, which plays crucial roles in both embryonic development and tumor metastasis, is characterized by the loss of epithelial markers and acquisition of mesenchymal markers (31)(32)(33). TGF-β, a pleiotropic cytokine, is a pivotal molecule in the EMT processing of tumor cells and can activate EMT-related transcription factors in both SMAD-dependent and SMAD-independent manners (21,22,34). It was confirmed that 10 ng/ml TGF-β could activate SMAD signaling and increase cellular migration in CRC cells by promoting reorganization of the actin cytoskeleton and upregulating vimentin expression.…”
Section: Discussionmentioning
confidence: 99%